Resilience Strategies of Islamic Religious Education Teachers in Facing Religious Diversity in Junior High School Students - Nicky Estu Putu Muchtar; Muhammad Arfan Mu'ammar; Evi Wiyanti (Fakultas Agama Islam Universitas Billfath, 2025)
This study aims to examine the resilience strategies of Islamic Education teachers in facing religious diversity at SMPN 1 Lamongan. This research employs a qualitative method with a case study approach. Data collection was conducted through interviews with two students and one Islamic Education teacher, as well as observations. The data analysis technique follows Creswell’s thematic analysis, which includes organizing data, coding, identifying code patterns, classifying, interpreting, and presenting data. The study ensures credibility through data triangulation. The findings indicate that the main challenge faced is the imbalance in the number of majority and minority religious students, which is addressed through classroom clustering. Although this approach poses a risk of segregation, the school principal mitigates it through various policies, such as (1) scripture memorization programs, (2) religious study forums, and (3) student involvement in academic, non-academic, and religious activities. Islamic Education teachers demonstrate resilience strategies, including emotional regulation and impulse control, self-efficacy, and optimism.